The Effect of Transformational Leadership and Worklife Balance on Employee Performance Mediated by Employee Commitment - Amira, Amira; Pratama, Galih Chandra; Rahmattullah, Yaumir; Abdullah, Tengku Mohd. Khairal (LPPM of NAROTAMA UNIVERSITY, 2024)
Competitive advantage is one of the most important factors to ensure a company continues to move forward. and one of the important factors that contributes to this is the performance of qualified employees. There has been a lot of research examining factors that influence employee performance, including transformational leadership, commitment and since Covid-19, the work-life balance factor has also been widely researched. Even though many studies have been carried out, many of the results of these studies are still inconclusive. This research seeks to contribute to the development of literature on these factors, especially in the context of PT KPP. This research was conducted at section up and senior manager levels who had attended leadership training at PT KPP. The sampling method used was purposive and from a total population of 140 people, 100 sample people had successfully returned the questionnaires given. The research results show that Transformational Leadership influences employee commitment, and Transformational Leadership factors also influence employee performance. Meanwhile, other proposed hypotheses have failed to be proven.